A standardised approach towards selecting forests for strict protection in Germany - Patricia Borel; Jan-Geert Bliefernicht; Eva Flinkerbusch; Martin Gutsch; Anke Höltermann; Ulrich Matthes; Mats Nieberg; Tobias Nowakowski; Max Tölle; Christopher P. O. Reyer (Regional Environmental Change, 2026)
Forests serve as key ecosystems for biodiversity conservation and climate change mitigation. The achievement of ambitious biodiversity targets, such as the EU Biodiversity Strategy’s target of strictly protecting 10% of the EU’s land area, requires the systematic identification of key forest areas for protection. However, clear guidance on selecting such forests is lacking. In this study, we address this issue by developing forest protection scenarios based on different conservation criteria and data from the third German National Forest Inventory. We used state-of-the-art indicators capturing different aspects of biodiversity: forest structure, habitat conservation, legal protection status, and the presence of old forests, alongside sociopolitical considerations including public ownership and equal distribution across federal states. Using a standardised, multi-criteria approach, we systematically identified forest areas for strict protection that best complied with each scenario’s criteria. Each scenario was then tested against three targets: strictly protecting 5%, 10%, and 30% of the total forest area. Our analysis revealed that, despite the application of different selection criteria in each scenario, the characteristics of the forests ultimately selected showed only moderate differences. Achieving higher protection targets, such as 10% or 30%, required including stands with lower conservation value, as evidenced by lower criterion overlap within selected forest areas. Although existing forest habitat types with no or minimal management requirements (i.e. 15.24% of German forest area) could theoretically serve as the selection pool for the 5% and 10% targets, sociopolitical considerations, such as having an equal spread of protected areas across federal states, required the incorporation of other forest areas. Overall, our findings provide a foundation for implementing Germany’s and the EU’s strict nature protection targets and demonstrate that multiple pathways exist to achieve them. However, strategic compromises may be required as the goals become more ambitious.